2005
DOI: 10.1097/01.mao.0000169796.83695.56
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Abnormalities in Patients with Goldenhar Syndrome

Abstract: Our observations regarding inner ear anomalies in Goldenhar syndrome correlate with the reported cases in the literature and may help to hypothesize the embryological origin of these malformations, which can caused by an early developmental arrest in the fourth gestational week. Specialists evaluating patients with Goldenhar syndrome should be aware of the possibility of inner ear malformations, which could be diagnosed earlier with appropriate imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
2
34
1
10
Order By: Relevance
“…This type of anomaly has been reported once in patients with the Goldenhar syndrome with a low frequency (36% of cases). 34 The high frequency of inner ear involvement in patients with OAVS and radial anomalies could suggest that this is a common clinical sign of this subset.…”
Section: Discussionmentioning
confidence: 99%
“…This type of anomaly has been reported once in patients with the Goldenhar syndrome with a low frequency (36% of cases). 34 The high frequency of inner ear involvement in patients with OAVS and radial anomalies could suggest that this is a common clinical sign of this subset.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains several descriptions of chromosomal anomalies and gestational exposure that mimic its phenotype (thalidomide, retinoic acid, and diabetes mellitus) 2 . Although external ear anomalies have been described in OAVS patients -to the point of being inclusion criteria -middle and especially inner ear alterations have received little attention in the literature [9][10][11][12][13] . Thus, the purpose of this study was to investigate the clinical findings in a sample of OAVS patients, focusing on ear alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of the third part of facial nerve was ascribed to petrous bone hypoplasia and to the semicircular canal hypoplasia. 10,11 The vestibule and cochlea hypoplasia was a sign of otic capsule anomalies. 10,11 All these osseous structures undergo a cartilagineous phase to reach a complete bone structure.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The vestibule and cochlea hypoplasia was a sign of otic capsule anomalies. 10,11 All these osseous structures undergo a cartilagineous phase to reach a complete bone structure. 3 Kay and Kay 9 demonstrated that an interference with cranial base chondrogenesis could be the cause of hemifacial microsomia: in OAVS cranio-facial development, interactions between NCCs and epithelial matrix are relevant in chondrogenesis as well as in osteogenesis; defects in cell differentiation or interaction may be present in the anlagen, leading to abnormal chondro-osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation